2022
DOI: 10.3390/economies10080179
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Non-Economic Factors on Voluntary Tax Compliance Behavior: A Case Study of Small and Medium Enterprises in Vietnam

Abstract: One of the main reasons governments of developing countries, including Vietnam, face many difficulties in tax collection is taxpayers’ non-compliance with taxes. Therefore, the question for the governments of these countries is how to encourage taxpayers to comply voluntarily without having to resort to mandatory measures. This study examines non-economic factors affecting the voluntary tax compliance behavior of small and medium enterprises (SMEs) in Vietnam. The data used in the study were collected from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…This emphasises the importance of psychological traits in tax compliance drives in emerging economies. This finding in Ghana also corroborates the positive effect of tax morale on tax compliance intentions (Alm, 2019;Lois et al, 2019;Taing & Chang, 2020;Timothy & Abbas, 2021) and that of tax tolerance (Al-Rahamneh & Bidin, 2022;Alshira'h & Abdul-Jabbar, 2019;Devos, 2014;Hassan et al, 2021;Muslichah & Graha, 2018;Nartey, 2023;Nguyen, 2022;Oladipo et al, 2022) in other economies.…”
Section: Discussion Of Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This emphasises the importance of psychological traits in tax compliance drives in emerging economies. This finding in Ghana also corroborates the positive effect of tax morale on tax compliance intentions (Alm, 2019;Lois et al, 2019;Taing & Chang, 2020;Timothy & Abbas, 2021) and that of tax tolerance (Al-Rahamneh & Bidin, 2022;Alshira'h & Abdul-Jabbar, 2019;Devos, 2014;Hassan et al, 2021;Muslichah & Graha, 2018;Nartey, 2023;Nguyen, 2022;Oladipo et al, 2022) in other economies.…”
Section: Discussion Of Resultssupporting
confidence: 72%
“…Devos (2014) noted that perception of unfairness in the tax system may cause tax evasion and taxpayers may use such unfairness to justify or rationalise their noncompliant behaviour. Again, perceived fairness of tax has been found to enhance tax compliance intention in Indonesia (Muslichah & Graha, 2018), Nigeria (Oladipo et al, 2022), Vietnam (Nguyen, 2022), Ghana (Nartey, 2023) and Jordan (Al‐Rahamneh & Bidin, 2022; Alshira'h & Abdul‐Jabbar, 2019). Hassan et al (2021) also finds that tax compliance simplicity has a positive impact on tax filing (Hassan et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Armah-Attoh and Awal (2013), Agyeiwaa et al . (2019) and Nguyen (2022) also revealed that knowledge drives tax compliance behaviour. Having knowledge of the tax process and tax regulations could help individuals honour their tax obligations without a glitch.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Pemeriksaan pajak secara menyeluruh dapat mendorong wajib pajak lebih berhati-hati dalam kepatuhan pajak. Wajib Pajak mengetahui akibat dan hukuman yang dapat merugikan, jika ditemukan ketidakpatuhan melalui pemeriksaan pajak, sehingga membuat wajib pajak memiliki rasa kepatuhan yang lebih baik (Nguyen, 2022).…”
Section: Pemeriksaan Pajakunclassified